2019
DOI: 10.1017/jfm.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of pressure losses and increase of mixing in laminar flows through channels with long-wavelength vibrations

Abstract: Pressure losses and mixing in vibrating channels were analysed. The vibrations in the form of long-wavelength travelling waves were considered. Significant reduction of pressure losses can be achieved using sufficiently fast waves propagating downstream, while significant increase of such losses is generated by waves propagating upstream. The mechanisms responsible for pressure losses were identified and discussed. The interaction of the pressure field with the waves can create a force which assists the fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Altering surface topography (Perot & Rothstein 2004) represents the former approach while the use of surface transpiration (Bewley & Alamo 2004; Min et al. 2006; Bewley 2009; Hœpffner & Fukagata 2009; Mamori, Iwamoto & Marata 2014), plasma- (Inasawa, Ninomiya & Asai 2013), sound- (Kato, Fukunishi & Kobayashi 1997) and piezo-driven actuators (Fukunishi & Ebina 2001) as well as surface vibrations (Floryan & Zandi 2019) represent the latter techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altering surface topography (Perot & Rothstein 2004) represents the former approach while the use of surface transpiration (Bewley & Alamo 2004; Min et al. 2006; Bewley 2009; Hœpffner & Fukagata 2009; Mamori, Iwamoto & Marata 2014), plasma- (Inasawa, Ninomiya & Asai 2013), sound- (Kato, Fukunishi & Kobayashi 1997) and piezo-driven actuators (Fukunishi & Ebina 2001) as well as surface vibrations (Floryan & Zandi 2019) represent the latter techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Min et al. (2006), Marusic, Joseph & Nahesh (2007) and Woodcock, Sader & Marusic (2012) demonstrated that a reduction of the pressure gradient can be achieved using suction/blowing waves but that the energy cost of the creation of such waves is higher than the energy savings associated with smaller pressure gradients (Bewley 2009; Fukagata, Sugiyama & Kasagi 2009). Transpiration can also increase losses through destabilization of the laminar flow (Lee, Min & Kim 2008; Lieu, Moarref & Jovanovič 2010; Moarref & Jovanovič 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An extension of this approach is based on the use of hydrophobic surfaces (Perot & Rothstein 2004). More active techniques involve the application of suitable distributed heating (Hossain, Floryan & Floryan 2012; Floryan & Floryan 2015; Floryan, Shadman & Hossain 2018), wall transpiration (Jiao & Floryan 2021), surface vibrations (Floryan & Zandi 2019), plasma actuators (Inasawa, Ninomiya & Asai 2013), sound (Kato, Fukunishi & Kobayashi 1997) or piezoelectric actuators (Fukunishi & Ebina 2001). An excellent review of some of these ideas has been given by Cattafesta & Sheplak (2011).…”
Section: Introductionmentioning
confidence: 99%
“…The creation of distributed forcing in technical systems involves the imposition of forcing patterns along fluid–solid boundaries to reduce the relative velocity of the two mediums. Known physical manifestations of these effects include nonlinear streaming created by wall transpiration (Jiao & Floryan 2021), the pattern interaction effect (Floryan & Inasawa 2021) that leads to thermal drift (Abtahi & Floryan 2017; Inasawa, Hara & Floryan 2021) and surface vibrations (Floryan & Zandi 2019). Flow relaminarization using transpiration waves (Lieu, Moarref & Jovanović 2010; Moarref & Jovanović 2010; Mamori, Iwamoto & Murata 2014; Kaithakkal, Kametani & Hasegawa 2020) or surface vibrations (Nakanishi, Mamori & Fukagata 2012; Nabae & Fukugata 2021) represent interesting alternatives for the control of turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
“…Active methods employ external body forces 17 , actuated particles 18 and various stirrers 9 with all of them requiring an external energy input. Three-dimensionality and unsteadiness do not guarantee chaos 19,20 , and not every chaotic state guarantees good stirring; either Poincaré maps or Lyapunov exponents must be used to verify whether the resulting flow is both chaos-and stirring-capable.…”
mentioning
confidence: 99%